Effects of Heat and Massage Applications to the Lumbosacral Area on Duration of Delivery and Perception of Labor Pain: A Randomized Controlled Experimental Trial - DURMUŞ, Ayşenur; ERYILMAZ, Gülşen (Marmara University, 2022)
Objective: This study was carried out to determine the effects of massage and hot-pack applications in the first stage of labor on perceptions of labor pain and duration of delivery. Methods: This randomized controlled experimental trial was conducted in an obstetrics and pediatrics hospital. The research sample comprised 120 pregnant women, 40 of whom were in the massage group, 40 of whom were in the hot-pack application group, and 40 of whom were in the control group. Patient identification forms, labor process monitoring forms, and a visual analogue scale (VAS) were used to collect data. Results: It was determined that the massage and hot-pack applications shortened the durations of the active and transition phases of labor. The massage and hot-pack applications also reduced perceptions of pain in the active and transition phases. Mean VAS scores of the massage and hot-pack application groups were lower than those of the control group (p
Keywords: Health Care Administration; Labor Pain; pain perception; pregnant women; massage; heat application; Sağlık Kurumları Yönetimi; pain perception; pregnant women; massage; heat application; 3. Good health